1996
DOI: 10.1200/jco.1996.14.7.2101
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine pretreatment for protection against cyclophosphamide-induced and cisplatin-induced toxicities: results of a randomized control trial in patients with advanced ovarian cancer.

Abstract: Pretreatment with amifostine reduces the cumulative hematologic, renal, and neurologic toxicities associated with the CP regimen, with no reduction in antitumor efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
185
3
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(201 citation statements)
references
References 54 publications
4
185
3
9
Order By: Relevance
“…Pre-existing hearing loss or chronic noise exposure clearly increases the risk for persisting auditory symptoms at least threefold, raising the question of clinical implications. Trials focusing on the ability of chemical substances, such as amifostine, to protect normal tissue from cisplatin toxicity are becoming increasingly important (Kemp et al, 1996). Future studies should prospectively evaluate the risk factors identified and use them as stratification criteria for clinical trials aiming at the prevention of cisplatin induced ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing hearing loss or chronic noise exposure clearly increases the risk for persisting auditory symptoms at least threefold, raising the question of clinical implications. Trials focusing on the ability of chemical substances, such as amifostine, to protect normal tissue from cisplatin toxicity are becoming increasingly important (Kemp et al, 1996). Future studies should prospectively evaluate the risk factors identified and use them as stratification criteria for clinical trials aiming at the prevention of cisplatin induced ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Large comparative clinical trials of amifostine in patients with advanced ovarian cancer (Kemp et al, 1996), rectal cancer (Liu et al, 1992), and head and neck cancer (Brizel et al, 2000) have been completed. These trials have shown that amifostine protects against the cytotoxic effects of cisplatin, cyclophosphamide, and radiation therapy.…”
mentioning
confidence: 99%
“…, and the evidence of its broad spectrum cytoprotective properties resulting in a reduction of both haematologic and organ toxicities without tumour protection (Kemp et al, 1996;Elias et al, 2000;Hartmann et al, 2000aHartmann et al, , 2000b. Preservation of renal function using the combination of cisplatin, ifosfamide and etoposide plus amifostine had been previously demonstrated (Hartmann et al, 1999b).…”
mentioning
confidence: 99%